Practical Cardiology Review a Self-Assessment Tool. - Alizadehasl, Azin (Cambridge Scholars Publisher, 2019)
This book is question-based, full of important clinical and practical points in cardiology, tables, images and movies. It fills a gap in the existing literature by providing a step-by-step educational and practical and clinical study, covering basic to advanced cardiology tips that would be helpful to all residents, fellows, and clinicians in cardiology, internal medicine, cardiac surgery, interventional cardiology, and pediatric cardiology around the world.